Advances in Environmental, Economic and Social Assessment of Energy Systems - Iribarren, Diego (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The overall energy sector calls for a transformation from a fossil-based system to a low-carbon one. At a technology level, significant efforts have been made to provide energy solutions that contribute to a sustainable energy system. However, the actual suitability of these solutions is often not checked. In this sense, the assessment of energy systems from a life-cycle perspective is of paramount importance when it comes to effectively planning the energy sector. While environmental issues are commonly addressed through the use of the Life Cycle Assessment (LCA) methodology, the comprehensive evaluation of the economic and social aspects of energy systems often remains ignored or underdeveloped. This book consists of a set of scientific works addressing the analysis of energy systems from a (life-cycle) technical, economic, environmental and/or social standpoint. Case studies at and beyond the technology level are included, some of them involving a combination of life cycle and non-life cycle approaches for the thorough evaluation of energy systems under the umbrella of sustainability.